Growth and yield of corn forage intercropped with marandu grass in an agrosilvopastoral system with eucalyptus - Domingues, Miguel Sales [UNESP]; Andrighetto, Cristiana [UNESP]; Lupatini, Gelci Carlos [UNESP]; Mateus, Gustavo Pavan; Aranha, Aline Sampaio [UNESP]; Ono, Rafael Keith; Shiguematsu, Mayara Mayumi Dos Santos [UNESP]; Giacomini, Polyana Vellone [UNESP]; Sekiya, Bianca Midori Souza [UNESP] (Universidade Estadual de Londrina, 2017)
Corn and grass intercropping is an interesting practice, and forage plants belonging to the genus Urochloa are the most commonly used in these situations. These plants show excellent adaptation to low-fertility soil, easy establishment, considerable biomass production, as well as being an important competitor with weeds. In agrosilvopastoral systems, the yield of corn crops grown together with trees is hindered due to the reduced radiation incidence caused by tree shading. This study aimed to evaluate corn growth, light interception, and chlorophyll content when intercropped with marandu grass in an agrosilvopastoral system with one and three eucalyptus rows, and compare them with plants under full sun. The experiment was conducted in Andradina - SP (Brazil). Treatments consisted of intercropping with no eucalyptus (plants under full sun: control), one system with one eucalyptus row and another with three rows. We also assessed the effect of five distances between corn plants and eucalyptus trees (2, 4, 6, 8, and 10 m). Between eucalyptus rows, corn plants were intercropped with marandu grass. The analyzed variables were corn plant height, ear height, chlorophyll content index, light interception, dry matter, and fresh and dry forage weights. The experimental design was a randomized block in a factorial scheme plus a control, with four repetitions. Tree arrangements had no influence on corn forage, dry matter, plant height, or ear height. Lower results of yield, dry matter, plant height, and ear height were observed for plants spaced 2 m from trees. In the first two evaluations, significant differences of light interception were found for the different distances. Neither tree arrangements (one and three rows) nor the distances from the trees had any impact on corn heights, with no difference between control and the agrosilvopastoral systems. Neither plant distances from trees nor tree arrangements had an influence on chlorophyll content index of corn plants, with no difference between control and the treatments. As a result, corn growth and forage yield under agroforestry systems are similar in arrangements of 1 and 3 eucalyptus rows (15-month-old trees) and under full sun. However, corn dry matter contents were lower in systems containing trees. Intercropping corn and marandu grass in a system without trees increased light interception at harvest time, indicating a larger soil coverage. Corn forage yield and dry matter content were lower when plants were 2 m apart from eucalyptus trees since this condition provided a lower amount of light and greater competition for water and nutrients.
Keywords: Crop-livestock-forest integration; Light interception; Shade; Urochloa brizantha; Zea mays